Asuhan Keperawatan Medical Bedah dengan Penerapan Teknik Effleurage terhadap Penurunan Intensitas Nyeri pada Pasien Post Appendiktomi di RSUD dr. T.C.Hillers Maumere - Yohana Nona Fadila Weo; Melkias Dikson (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Background: Health is something that is very important for human life. Health and lifestyle are influenced by developments over time. One example is the lack of consumption of foods with fiber to meet daily needs, which causes health problems, namely appendicitis. Appendicitis is a common cause of acute inflammation of the right lower quadrant of the abdominal cavity, which is treated by emergency abdominal surgery. The inflammatory process that occurs in the appendix increases intraluminal pressure which causes the pain to become more severe, generalized or periumbilical and move to the right lower quadrant. One way to deal with pain is by applying the effleurage technique (massage/touch therapy). The aim of this case study is to determine the reduction in pain scale in post-appendectomy patients after effleurage technique therapy (massage/touch therapy). The method used in this case study is case study design with a nursing care process approach. The subjects in this case study were 2 patients, who were obtained from inclusion and exclusion criteria, data collection using the numeric rating scale (NRS). The results of the case study show that the average pain level of the two patients after being given effleurage technique therapy intervention (massage/touch therapy) for 3 days experienced a change from moderate pain to mild pain. The conclusion of this case study shows that there were changes that occurred after the effleurage technique (massage/touch therapy) was given to the 2 patients and they experienced a decrease in the pain scale.